Habitual intake of dietary advanced glycation end products is not associated with generalized microvascular function—the Maastricht Study. Issue 2 (28th September 2021) - Linkens, Armand M A; Houben, Alfons J H M; Kroon, Abraham A; Schram, Miranda T; Berendschot, Tos T J M; Webers, Carroll A B; van Greevenbroek, Marleen; Henry, Ronald M A; de Galan, Bastiaan; Stehouwer, Coen D A; Eussen, Simone J M P; Schalkwijk, Casper G
ABSTRACT: Background: Endogenously formed advanced glycation end products (AGEs) may be important drivers of microvascular dysfunction and the microvascular complications of diabetes. AGEs are also formed in food products, especially during preparation methods involving dry heat. Objectives: We aimed to assess cross-sectional associations between dietary AGE intake and generalized microvascular function in a population-based cohort. Methods: In 3144 participants of the Maastricht Study (mean ± SD age: 60 ± 8 y, 51% men) the dietary AGEs N ε -(carboxymethyl)lysine (CML), N ε -(1-carboxyethyl)lysine (CEL), and N δ -(5-hydro-5-methyl-4-imidazolon-2-yl)-ornithine (MG-H1) were estimated using the combination of our ultra-performance LC–tandem MS dietary AGE database and an FFQ. Microvascular function was determined in the retina as flicker light–induced arteriolar and venular dilation and as central retinal arteriolar and venular equivalents, in plasma as a z score of endothelial dysfunction biomarkers (soluble vascular adhesion molecule 1 and soluble intracellular adhesion molecule 1, soluble E-selectin, and von Willebrand factor), in skin as the heat-induced skin hyperemic response, and in urine as 24-h albuminuria. Associations were evaluated using multiple linear regression adjusting for demographic, cardiovascular, lifestyle, and dietary factors. Results: Overall, intakes of CML, CEL, and MG-H1 were not associated with the microvascular outcomes. Although higher intake of CEL was associated with higher flicker light–induced venular dilation (β percentage change over baseline: 0.14; 95% CI: 0.02, 0.26) and lower plasma biomarker z score (β: −0.04 SD; 95% CI: −0.08, −0.00 SD), the effect sizes were small and their biological relevance can be questioned. Conclusions: We did not show any strong association between habitual intake of dietary AGEs and generalized microvascular function. The contribution of dietary AGEs to generalized microvascular function should be further assessed in randomized controlled trials using specifically designed dietary interventions.